Analysis of Calcium Content in Tuna Bones Using an Enzymatic Method - I M.W. Wijaya; Erni Mohammad; Najmah Najmah; Netty I. Ischak; Arviani Arviani (Universitas Tadulako, 2026)
Bone waste of mackerel tuna (Euthynnus affinis) has great potential as a natural source of calcium. The enzymatic approach using papain offers a safe, environmentally friendly method for green extraction. This study aims to evaluate the effects of variations in papain concentration on the yield and calcium content of cod fish bone hydrolysis. The method used was a one-factor Complete Random Design with four levels of papain concentration (6, 8, 10, and 12 %) and three replicates. Hydrolysis is carried out at 60 °C and pH 6.5 for 4 hours. Calcium levels were analyzed using an Atomic Absorption Spectrophotometer (SSA) at a wavelength of 422 nm. ANOVA showed that papain concentration had a significant effect on yield (p < 0.05) but not on calcium content (p > 0.05). The highest yield, 105.66%, was obtained at a 6% concentration and was influenced by post-hydrolysis water retention and residual salt retention from the buffer solution. Meanwhile, the highest calcium release was achieved at a 10% concentration of 165.63 mg/g. Hydrolysis with papain has been shown to effectively degrade the collagen matrix, releasing minerals without damaging the bone's hydroxyapatite structure. Implicitly, this study offers an efficient method for the fishery waste treatment industry to produce alternative calcium supplements, while guiding the optimization of enzyme dosage based on production-target priorities.